2020
DOI: 10.1101/2020.06.22.160168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial retrons encode tripartite toxin/antitoxin systems

Abstract: 19Retrons are genetic retroelements, commonly found in bacterial genomes and recently 20 repurposed as genome editing tools. Their encoded reverse transcriptase (RT) produces a 21 multi-copy single-stranded DNA (msDNA). Despite our understanding of their complex 22 biosynthesis, the function of msDNAs and therefore, the physiological role of retrons has 23 remained elusive. We establish that the retron-Sen2 in Salmonella Typhimurium encodes a 24 toxin, which we have renamed as RcaT (Retron cold-anaerobic Toxin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 53 publications
3
29
0
7
Order By: Relevance
“…This suggests that most of the diverse genetic systems encoded at this hotspot are involved in anti-phage defense. A retron from E. coli E101 associated with a transmembrane effector protected against P1vir and 186cIts, as expected from previous findings (7,8,18,37). Among unknown systems with known defense domains, we identified a HEPN-family protein as well as other single-protein systems that comprise either an AAA+ ATPase, a sirtuin (SIR2) or a toll/interleukin-1-receptor-like (TIR) domain.…”
Section: P4-like Satellite Phages Encode a Hotspot For Bacterial Immusupporting
confidence: 84%
See 1 more Smart Citation
“…This suggests that most of the diverse genetic systems encoded at this hotspot are involved in anti-phage defense. A retron from E. coli E101 associated with a transmembrane effector protected against P1vir and 186cIts, as expected from previous findings (7,8,18,37). Among unknown systems with known defense domains, we identified a HEPN-family protein as well as other single-protein systems that comprise either an AAA+ ATPase, a sirtuin (SIR2) or a toll/interleukin-1-receptor-like (TIR) domain.…”
Section: P4-like Satellite Phages Encode a Hotspot For Bacterial Immusupporting
confidence: 84%
“…1B, Table S2). They can be broadly grouped into three categories : (i) known defense systems such as a type-III restriction enzyme, the type-II EcoO109I RM system (39), retrons (7,8,18,37), Gabija (17) or Septu (17); (ii) uncharacterized systems with protein domains that were previously associated with bacterial immunity such as SIR2 (17,41), TIR (17) and HEPN (18,42); (iii) systems encoding proteins with no annotated domain or whose domain is currently not associated with anti-phage defense, such as NACHT and various domains of unknown function (DUFs). Based on these observations, we hypothesized that the P4-encoded locus between psu and int may constitute a reservoir of bacterial immune systems that likely participate in interviral competition.…”
Section: P4-like Satellite Phages Encode a Hotspot For Bacterial Immumentioning
confidence: 99%
“…Recently, it was reported that some retrons members of the type systems I-A (Retron+ATPase+HNH), II-A3 (Nuc_deoxy+Retron), I-C1 (Retron-Toprim) and XII (Retron-TIR) defined here mediate antiphage defense and that the additional proteins or RT-fused domains are also required for activity ( 81 ). Moreover, a recent report ( 82 ) and two pre-prints ( 83 , 84 ) have also suggested that retrons may be novel anti-phage defense systems and that they may function as a toxin/antitoxin system. The first of these roles is thought to be mediated by the RT and msDNA, with the linked effector protein responsible for toxin/antitoxin functions.…”
Section: Discussionmentioning
confidence: 99%
“…This reverse transcribed DNA (RT-DNA) is produced in cells from a universally delivered cassette in high abundance such that it overcomes inefficiencies and increases rates of genome editing. One retroelement class that has been useful in this regard are bacterial retrons 6,8,9 , which are elements involved in phage defense [10][11][12][13] . Retrons are attractive as a biotechnology due to their compact size, tightly defined sites of RT initiation and termination, lack of known host factor requirements, and lack of transposable elements.…”
Section: Introductionmentioning
confidence: 99%